BOGDANOV-TAKENS BIFURCATIONS IN THREE COUPLED OSCILLATORS SYSTEM WITH ENERGY PRESERVING NONLINEARITY - Livia Owen; J.M. Tuwankotta (Journal of the Indonesian Mathematical Society, 2012)
looked at pdf abstractDOI : http://dx.doi.org/10.22342/jims.18.2.113.73-83